Rapid Neurologic Improvement Predicts Favorable Outcome 90 Days After Thrombectomy in the DEFUSE 3 Study. Issue 5 (May 2019) - Heit, Jeremy J.; Mlynash, Michael; Kemp, Stephanie M.; Lansberg, Maarten G.; Christensen, Soren; Marks, Michael P.; Ortega-Gutierrez, Santiago; Albers, Gregory W.
Abstract : Background and Purpose—: Thrombectomy in late time windows leads to improved outcomes in patients with ischemic stroke due to large vessel occlusion. We determined whether patients with rapid neurological improvement (RNI) 24 hours after thrombectomy were more likely to have a favorable clinical outcome in the DEFUSE 3 study (Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke 3). Methods—: All patients who underwent thrombectomy in DEFUSE 3 were included. RNI was defined as a reduction of ≥8 on the National Institutes of Health Stroke Scale or National Institutes of Health Stroke Scale zero to one 24 hours after thrombectomy. Clinical outcomes were assessed by an ordinal analysis modified Rankin Scale score and a dichotomous analysis for 90-day independence (modified Rankin Scale score, 0–2). Results—: Ninety-one patients in DEFUSE 3 underwent thrombectomy with follow-up data; 31 patients (34%) experienced RNI (RNI+) after thrombectomy and 60 patients (66%) did not (RNI−). Patient demographics and stroke presentation and imaging details were similar between RNI+ and RNI− patients. Reperfusion (Thrombolysis in Cerebral Infarction 2b-3) after thrombectomy was achieved in 26 (84%) RNI+ and 43 (72%) RNI− ( P =0.2). Symptomatic intracranial hemorrhage occurred in no RNI+ and 8% of RNI− patients ( P =0.2). RNI was associated with a favorable modified Rankin Scale shift at day 90 (odds ratio, 3.8; CI, 1.7–8.6; P =0.001) and higher rates of modified Rankin Scale zero to 2 (61% versus 37%; odds ratio, 2.7; CI, 1.1–6.7; P =0.03). Mortality was 3% in RNI+ versus 18% in RNI− ( P =0.05). RNI+ patients had lower median 24-hour National Institutes of Health Stroke Scale (5 [interquartile range (IQR), 1–7] versus 13 [IQR, 7.5–21]; P <0.001), smaller 24-hour infarction volume (21 [IQR, 5–32] versus 65 [IQR, 27–145] mL; P <0.001), and less 24-hour infarct growth (8 [IQR, 1–18] versus 37 [IQR, 16–105] mL; P <0.001) compared with RNI− patients. Hospital stay was shorter in RNI+ (3.7 [IQR, 2.9–7.1] versus 7.4 [IQR, 5.2–12.1] days in RNI−; P <0.001). Conclusions—: RNI following thrombectomy correlates with favorable clinical and radiographic outcomes and reduced hospital length of stay. RNI was a favorable prognostic sign following late-window thrombectomy in DEFUSE 3. Clinical Trial Registration—: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02586415.